Critical Thinking Ability Reviewed from Epistemic Curiosity Interest Type in Comic-Assisted Learning (Unnes Journal of Mathematics Education Research, 2022)
Students’ different ability in receiving information indicates that they have varying critical thinking skills. This study aims to describe the ability to think critically in terms of epistemic curiosity type of interest in learning models of Problem Based Learning class VIII about two-variable linear equation system material. The research design is a method of mixed triangulation-concurrent with the type of Mix-Method research. The findings in this study showed that teaching-learning process in this study was not qualified. Poor quality of learning results was caused by several obstacles during research, such as technical implementation, time allocation, learning preparation and have implications for the research results that do not have good quality, so descriptions of students' critical thinking skills with epistemical curiosity of high, medium, and low categories are invalid and mathematical critical thinking skills of students with each of these categories can not be measured.